LEVERAGING GREEN FINANCING FOR SUSTAINABLE RURAL DEVELOPMENT IN AFRICA: A BIBLIOMETRIC ANALYSIS OF LITERATURE - Shadreck Nhorito; Manhando Tendai (Multifinance, 2025)
The study focused on leveraging green financing for sustainable rural development in Africa. The bibliometric analysis of literature relating to the study was utilised through developing themes relating to the specific objectives of the study. The problem of the study is limited green financing in rural Africa due to lack of social justice by the responsible leaders when allocating finances for sustainable development. The specific objectives of the study are to establish the factors influencing green financing for sustainable rural development in Africa, to analyse the impact of green financing for sustainable rural development, to assess the challenges for leveraging green financing for sustainable rural development, and to establish strategies for leveraging green financing for sustainable rural development. The study was guided by the Capability Approach emphasizing on how people can understand the existence of unequal distribution of resources due to the destruction of capability and functioning of the members of the household. The result from literature shows that policy clarity, taxonomies, stable regulations and alignment with the global climate-finance architecture strongly influence green financing in rural Africa. Inclusive green growth pathway. National transitions that integrate skills, SMEs, and gender inclusion into green-finance programs tend to yield broader rural welfare improvements financial-sector constraints. Green-banking is limited by awareness, perceived complexity, and lack of dedicated funds, curbing diffusion in rural enterprises.